(untitled) (Indian Journal of Case Reports, 2021)
Renal lymphangiectasia is a rare entity occurring both in children and adults with no specific age preference. It may be unilateral or bilateral and has no gender predilection. The clinical symptoms are non-specific ranging from no complaints with incidental diagnosis to pain abdomen. Radiological appearance may be mistaken with peripelvic cysts, renal cysts, and perinephric abscess, or collection. Hence, here lies the importance of familiarity with imaging appearance of this rare condition. We describe the case of a 35-year-old male who presented with pain abdomen. The radiological investigations revealed bilateral perinephric collections which led to the diagnosis of bilateral renal lymphangiectasia by exclusion, which was confirmed by aspiration of chylous fluid.